Incorporation of in vitro digestive enzymes in an intestinal epithelial cell line model for protein hazard identification. (October 2017) - Markell, Lauren K.; Wezalis, Stephanie M.; Roper, Jason M.; Zimmermann, Cindi; Delaney, Bryan
Abstract: Relatively few proteins in nature produce adverse effects following oral exposure. Of those that do, effects are often observed in the gut, particularly on intestinal epithelial cells (IEC). Previous studies reported that addition of protein toxins to IEC lines disrupted monolayer integrity but innocuous dietary proteins did not. Studies presented here investigated the effects of innocuous (bovine serum albumin, β-lactoglobulin, RuBisCO, fibronectin) or hazardous (phytohaemagglutinin-E, concanavalin A, wheat germ agglutinin, melittin) proteins that either were untreated or exposed to digestive enzymes prior to addition to Caco-2 human IEC line monolayers. At high concentrations intact fibronectin caused an increase in monolayer permeability but other innocuous proteins did not whether exposed to digestive enzymes or not. In contrast, all untreated hazardous proteins and those that were resistant to digestion (ex. wheat germ agglutinin) disrupted monolayer integrity. However, proteins sensitive to degradation by digestive enzymes (ex. melittin) did not adversely affect monolayers when exposed to these enzymes prior to addition to IEC line monolayers. These results indicate that in vitro exposure of proteins to digestive enzymes can assist in differentiating between innocuous and hazardous proteins as another component to consider in the overall weight of evidence approach in protein hazard assessment. Graphical abstract: Highlights: A Caco-2 human intestinal cell line monolayer is proposed to differentiate between hazardous and innocuous proteins. Monolayer tight junction integrity was the most sensitive indicator. Exposure to digestive enzymes can support protein hazard identification.